2013
DOI: 10.3201/eid1904.120903
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Hotspots for Influenza Virus Reassortment

Abstract: TOC summary: Reassortment is most likely to occur in eastern China, central China, or the Nile Delta in Egypt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 33 publications
(41 reference statements)
1
61
0
Order By: Relevance
“…The importance of the east coastal region as the hotspot of avian influenza outbreaks is supported by previous studies: The potential hotspots for H5N1 reassortment being identified in previous studies are the coastal provinces [52]; HPAI H5N1 risk distributions are identified in both south and north of the YRD [2]. In addition, the recent H7N9 outbreaks occurred initially in the YRD, and then spread along both south and north of the East Coast lines [20].…”
Section: Discussionmentioning
confidence: 65%
“…The importance of the east coastal region as the hotspot of avian influenza outbreaks is supported by previous studies: The potential hotspots for H5N1 reassortment being identified in previous studies are the coastal provinces [52]; HPAI H5N1 risk distributions are identified in both south and north of the YRD [2]. In addition, the recent H7N9 outbreaks occurred initially in the YRD, and then spread along both south and north of the East Coast lines [20].…”
Section: Discussionmentioning
confidence: 65%
“…61,164,165 The infection is concentrated mainly in the Nile Delta, the influenza epicentre in Egypt. 15,155,166 Fortunately, the vast majority of the Egyptian strains are sensitive to the NA inhibitor oseltamivir 55,61,166,167 which may also explain the lower case-fatality rate of H5N1 in human in Egypt. Nevertheless, the continuous evolution of H5N1 in Egypt makes it a potential candidate for being a possible pandemic virus.…”
Section: H5n1mentioning
confidence: 99%
“…11 Although many countries successfully eradicated the HPAIV H5N1 from poultry, Egypt, China, Vietnam, Bangladesh, Cambodia and Indonesia were declared as H5N1-endemic countries. 12 Egypt is considered a hotspot for the evolution of a pandemic potential virus either via antigenic drift of the H5N1 to increase its adaptation to humans 13,14 or through reassortment with other IAV subtypes, especially H3N2 virus 15 or H9N2. 16 Egypt has experienced several waves of IAV since 1900s.…”
Section: Introductionmentioning
confidence: 99%
“…Reassortment between H9N2 and H5N1 viruses in Egypt is anticipated due to the increasingly parallel occurrence of these viruses in poultry holdings Kayali et al, 2014). Phenotypic properties of such reassortants cannot be predicted, however, given the impact of internal gene segments of H9N2 in the generation of highly zoonotic AIV in China the timely detection of such reassortants is certainly a matter of concern for public health (Fuller et al, 2013). Therefore, molecular methods that allow the identification of such reassortants directly from clinical poultry samples have to be developed and validated.…”
Section: Introductionmentioning
confidence: 97%